Simulation of particles screening in pulsating negative pressure shale shaker by coupling CFD and DEM. Issue 5 (19th November 2021) - Yin, Peng; Hou, Yongjun; Wu, Xianjin
Abstract : Purpose: The purpose of this paper is to obtain the combination of working parameters suitable for pulsating negative pressure shale shaker through simulation, which is conducive to efficient recovery of clean drilling fluid and relatively dry cuttings. Design/methodology/approach: Shale shaker is still one of the main equipment in solid–solid and solid–liquid separation processes in drilling industry. This research is based on a new drilling fluids circulation treatment device, namely pulsating negative pressure shale shaker. In this work, a numerical study of particle flow and separation in the pulsating negative pressure shale shaker is carried out by coupling computational fluid dynamics /discrete element method (CFD-DEM). The effect of vibration parameters and negative pressure parameters are studied in terms of conveyance velocity and percent through screen. Findings: The results show that, conveyance velocity of particle is mainly affected by vibration parameters, negative pressure in pulsating form can effectively prevent cuttings from sticking to the screen. Vibration parameters and pulsating airflow velocity peak have great influence on percent through screen, while vibration frequency and screen slope have influence on the time when the percent through screen reaches stability. Originality/value: In this paper, the authors put forward a new kind of drilling waste fluid treatment equipment, and focused on the study of particle movement law. The results have important guiding significance for the selection of structural design parameters and rational use of equipment. In addition, the new device provides a new idea for solid–liquid separation method, which is one of the hot topics in current research.